Microsoft Surface - Blecher, Joni (Visual quickstart guide., 2013)
This Visual QuickStart Guide will help you get up and running with the Surface, Microsoft's very-own entry into the tablet market. This guide walks you through how to get the most from the Surface, using four-color images and step-by-step instruction. You'll learn how to tap and swipe, search, find the best Metro apps, read books, watch movies, listen to songs, and use Office. Along the way, you'll pick up indispensable tips for getting the most out of your tablet.